Syntactic and semantic features of nursing terminology in English / Luu Thi Hang; NHDKH Assoc. Prof. Dr. Phan Van Que - Luu, Thi Hang
Research purposes: This study aims at identifying the syntactic and semantic features of nursing terminologies in English in order to help learners of English memorizing nursing terminologies in English in terms of syntactic and semantic features effectively. Methods of the study: The descriptive, contrastive analysis and synthetic methods in combination with the data collection and data analysis techniques. Results of the research: In terms of syntactic features, the formation of nursing terminologies at word level between English and Vietnamese has certain similarities and differences of word type, phrasal structure and collocation. In terms of semantic features, the English - Vietnamese nursing terminology shows many similarities in the identifying the meaningful characteristics as well as their structural model. Furthermore, some implications are suggested for teaching and learning the English nursing terminologies. Conclusions: This thesis has focused on studying the syntactic and semantic features of nursing terminology in English to find out their similarities and differences. Due to the limitation of time, research data and the limited knowledge of the author, mistakes and shortcoming are unavoidable. As a result, suggestions for a further study are given.